(untitled) (European Journal of Emerging Technology and Discoveries, 2023)
This article explores the pedagogical approaches based on artificial intelligence (AI) that are transforming education by enabling personalized learning and fostering student success. With advancements in AI, educators now have access to innovative tools and technologies that can adapt instruction to individual students’ needs, preferences, and learning styles. This article delves into various AI-based pedagogical approaches, including adaptive learning platforms, intelligent tutoring systems, and personalized recommendation systems. It examines the benefits and challenges associated with personalized learning through AI and emphasizes the impact on student success. Furthermore, ethical considerations surrounding the use of AI in education are discussed. By harnessing the power of AI, educators can create tailored learning experiences, enhance engagement and motivation, and improve learning outcomes, ultimately leading to increased student success.